Enantioselective reductive cross-couplings to forge C(sp2)–C(sp3) bonds by merging electrochemistry with nickel catalysis - Yun-Zhao Wang; Bing Sun; Jian-Feng Guo; Xiao-Yu Zhu; Yu-Cheng Gu; Ya-Ping Han; Cong Ma; Tian-Sheng Mei (Nature Communications)
Abstract Motivated by the inherent benefits of synergistically combining electrochemical methodologies with nickel catalysis, we present here a Ni-catalyzed enantioselective electroreductive cross-coupling of benzyl chlorides with aryl halides, yielding chiral 1,1-diaryl compounds with good to excellent enantioselectivity. This catalytic reaction can not only be applied to aryl chlorides/bromides, which are challenging to access by other means, but also to benzyl chlorides containing silicon groups. Additionally, the absence of a sacrificial anode lays a foundation for scalability. The combination of cyclic voltammetry analysis with electrode potential studies suggests that NiI species activate aryl halides via oxidative addition and alkyl chlorides via single electron transfer.